0804 Behavioral and Sleep Problems in Children with ASD: Examining the Associated Risk of Poor Health in Caregivers. (27th April 2018) - Davenport, M; Munoz, M; Mazurek, M; McClean, D; Sahota, P; McCrae, C S
Abstract: Introduction: Sleep difficulties (40–80%) and disruptive behavior (25%) are common comorbidities in children with autism spectrum disorder (ASD). Research suggests that these comorbidities contribute to poor caregiver health. However, studies to date have focused largely on mothers and used nonrepresentative samples. Using a large representative sample, this study aimed to determine whether caregivers (mothers and fathers) of children with ASD and comorbid sleep difficulty and disruptive behavior are more likely to report poor physical health than caregivers of children with ASD without these comorbidities. Methods: The study utilized data from the 2011–2012 National Survey of Child Health. Data on demographics, child sleep and behavior, and caregiver health were reported by 936 caregivers of children with ASD (6–17 yrs, M age=11.48, SD=3.34: 81.4% male, 78.3% White). Caregivers reported on: their child's number of days of adequate sleep/week (coded as poor [≤4 days/week] or adequate [>4 days/week]); presence or absence of disruptive behavior disorder (DBD); and rated fathers' and mothers' health as poor/fair or excellent/good. Results: Two logistic regression models examined whether these comorbidities predict caregiver health, controlling for child race, sex, and age. Both models showed no significant interaction effects of poor sleep x DBD (Father-p =.07; Mother-p =.37), however significant main effects were found. Fathers of children with DBD were 3x more likely to report poor health than fathers of children without DBD (OR=3.06, 95% CI=1.83, 5.11, p=.00). Similarly, fathers of children with poor sleep were 3x more likely to report poor health than fathers of children with good sleep (OR=3.09, 95% CI=1.74, 5.48, p=.00). Mothers of children with both comorbidities were 2-3x more likely to report poor health (DBD-OR =2.46, 95% CI=1.55, 3.91, p =.00; sleep-OR =3.33, 95% CI =2.03, 5.46, p =.00). Conclusion: Both poor sleep and disruptive behaviors among children with ASD increased the likelihood of poor caregiver health. Caregivers of children with ASD with co-occurring sleep and behavioral problems may require additional health services and support. Support (If Any): Database from 2011–12 NSCH. Child and Adolescent Health Measurement Initiative.